Effects of music therapy on psychological distress of neurosurgical patients : a systematic review - Divaasini Devaraj,; Mahadir Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Neurosurgery has been on the rise, with a yearly estimate of 13.8 million patients suffering from neurological disorders or injuries and require surgery. Psychological distress is relatively frequent in neurosurgical patients due numerous threats and challenges faced therefore, the main objective of this review is to understand the efficiency of music therapy on neurosurgical patients in reducing psychological distress. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was used to guide the methodology of this systematic review. The PICO format was used as a search strategy in terms of specifying search terms and clarifying limits in relation to the population or intervention studied in this review. Databases like SCOPUS, MEDLINE and OVID, The Cochrane Library was utilized to search for relevant records. A total of 48 studies were identified through the databases search. After the removal of duplicates, 39 studies’ titles and abstracts were screened. Through a process of assessing eligibility, 5 studies were consequently included in the review. The year limits for the articles reviewed were 2015 to present, to highlight the more recent findings on the subject. The studies included in this review encompass different countries of origin such as USA, Canada and in Asia, Taiwan, China and India. The findings of this review show that music therapy is an effective intervention in reducing psychological distress, especially anxiety, in neurosurgical patients. Music therapy is also effective as an adjunct therapy for neurosurgical procedures. The cultural aspects infused in music therapy were also discussed in this paper.